Boiling as a mechanism for colour zonations observed at the Byrud emerald deposit, Eidsvoll, Norway: fluid inclusion, stable isotope and Ar–Ar studies. Issue 4 (15th July 2013) - Loughrey, L.; Marshall, D.; Ihlen, P.; Jones, P.
Abstract: The Byrud emerald deposit comprises pegmatite veins hosted within Cambrian black shales and Late Carboniferous quartz syenite sills intruded by a Permo‐Triassic riebeckite granite. The emerald deposit genesis is consistent with a typical granite‐related emerald vein system derived from dominantly magmatic fluids with minor contributions from metamorphic source(s). Muscovite from an emerald‐bearing pegmatite at Byrud yielded an excellent Ar–Ar plateau age of 233.4 ± 2.0 Ma. Emerald display colour zonation alternating between emerald and beryl. Two dominant fluid inclusions types are identified as follows: two‐phase (vapour+liquid) and three‐phase (brine+vapour+halite) fluid inclusions and these are interpreted to represent conjugate fluids of a boiling system. The emerald was precipitated from these saline fluids with approximate overall salinities on the order of 31 mass per cent NaCl equivalent. Raman analyses indicate molar gas fractions for CO2, N2, CH4 and H2 S are approximately 0.8974, 0.0261, 0.0354 and 0.0410, respectively. Formational temperatures and pressures of approximately 160–385°C and below 1000 bars were derived from fluid inclusion data and lithostatic pressure estimates from fluid inclusion studies within the Oslo rift. The colour zonation observed in the Byrud emerald crystals is related to alternating emerald and beryl precipitation in the liquid and vapour portions, respectively, of a two‐phase (boiling) system. Abstract : This study provides a model for the alternating emerald versus colourless beryl growth zones observed in emerald crystals from the Byrud deposit in Norway. These growth zones are host to a number of primary fluid inclusions and are related to alternating emerald and beryl precipitation in the liquid and vapour portions, respectively, of a two‐phase (boiling) system.